Renal Implications of Psoriasis: Urinary Podocyte Markers and Disease Progression - Sule Gencoglu; Meltem Yardim; Ramazan Fazil Akkoc (Dermatology Practical & Conceptual)
Introduction: Psoriasis may lead to glomerular inflammatory damage and disruption of the podocyte barrier, allowing podocyte degradation products to leak into the urine.